Can Ulcerative Dermal Necrosis (UDN) in Atlantic salmon be attributed to ultraviolet radiation and secondary Saprolegnia parasitica infections?. (June 2022) - Henard, Cyril; Saraiva, Marcia R.; Ściślak, Magdalena E.; Ruba, Tahmina; McLaggan, Debbie; Noguera, Patricia; van West, Pieter
Abstract: Ulcerative dermal necrosis (UDN), a chronic skin condition, affects primarily mature wild salmonids returning from the sea to freshwater for their spawning. The involvement of water moulds such as Saprolegnia parasitica as a secondary pathogen in this disease is clear but the identification of a primary cause or of primary pathogen(s) remains elusive. In this opinion article, we re-visit UDN regarding epidemiology, pathology and aetiology and speculate the potential involvement of UV radiation in the initiation of UDN in salmonid fish returning from the sea.